2008
DOI: 10.1021/nl801288d
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Metal−Insulator Transitions in Metallic Single-Walled Carbon Nanotubes

Abstract: We report on reversible metal to insulator transitions in metallic single-walled carbon nanotube devices induced by repeated electron irradiation of a nanotube segment. The transition from a low-resistive, metallic state to a high-resistive, insulating state by 3 orders of magnitude was monitored by electron transport measurements. Application of a large voltage bias leads to a transition back to the original metallic state. Both states are stable in time, and transitions are fully reversible and reproducible.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 18 publications
2
31
0
Order By: Relevance
“…The superscript "a" means "armchair". Figure 14 shows the band structure of three types of armchair nanotubes: (3,3), (5,5) and (9,9). Also shown is the general band region for armchair nanotubes with red representing the conduction band and blue representing the valence band.…”
Section: Carbon Nanotube Band Structurementioning
confidence: 99%
See 2 more Smart Citations
“…The superscript "a" means "armchair". Figure 14 shows the band structure of three types of armchair nanotubes: (3,3), (5,5) and (9,9). Also shown is the general band region for armchair nanotubes with red representing the conduction band and blue representing the valence band.…”
Section: Carbon Nanotube Band Structurementioning
confidence: 99%
“…An illustration of the band structure for zigzag type nanotubes is given in Figure 16 showing the band structure of six (n,0) zig-zag nanotubes where n = 5,6,7,8,9,10. The band structures of (6, 0) and (9, 0) have no band gap while those of (5, 0), (7,0), (8,0) and (10,0) show a band gap.…”
Section: Carbon Nanotube Band Structurementioning
confidence: 99%
See 1 more Smart Citation
“…A moderate irradiation can convert the room temperature electric properties of a metallic SWNT to semiconducting [4]. An intensive irradiation finally makes a SWNT almost insulating [5][6][7][8]. The decreased conductivity with the irradiation, as well as the degraded Raman and PL spectra, can recover reversibly by annealing [1,3,6] or applying a high bias to the SWNTs [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Although the irradiation-induced conductivity decreases in a SWNT and its recovery have been experimentally well established [5][6][7][8], the origin of the conductivity decrease is still controversial. We have reported that the irradiation-induced physical property changes are caused by defects created by the irradiation (low-energy irradiation damage) [6].…”
Section: Introductionmentioning
confidence: 99%